Understanding Idiopathic Interstitial Pneumonia: A Gene-Based Review of Stressed Lungs. (11th October 2015) - van Moorsel, Coline H. M.; Hoffman, Thijs W.; van Batenburg, Aernoud A.; Klay, Dymph; van der Vis, Joanne J.; Grutters, Jan C.
Abstract : Pulmonary fibrosis is the main cause of severe morbidity and mortality in idiopathic interstitial pneumonias (IIP). In the past years, there has been major progress in the discovery of genetic factors that contribute to disease. Genes with highly penetrant mutations or strongly predisposing common risk alleles have been identified in familial and sporadic IIP. This review summarizes genes harbouring causative rare mutations and replicated common predisposing alleles. To date, rare mutations in nine different genes and five risk alleles fulfil this criterion. Mutated genes represent three genes involved in surfactant homeostasis and six genes involved in telomere maintenance. We summarize gene function, gene expressing cells, and pathological consequences of genetic alterations associated with disease. Consequences of the genetic alteration include dysfunctional surfactant processing, ER stress, immune dysregulation, and maintenance of telomere length. Biological evidence shows that these processes point towards a central role for alveolar epithelial type II cell dysfunction. However, tabulation also shows that function and consequence of most common risk alleles are not known. Most importantly, the predisposition of the MUC5B risk allele to disease is not understood. We propose a mechanism whereby MUC5B decreases surface tension lowering capacity of alveolar surfactant at areas with maximal mechanical stress.